Democratization of conflict from school. Notes on peace education. - Acosta, Sandra (Universidad Distrital Francisco José de Caldas, 2016)
This article attempts to vindicate the school system as one of the scenarios that the more they can contribute to the achievement and sustainability of the processes that tend to make peace in the country. It was built under the conception that the only way to peace is the recognition of conflict as an inherent element of human relations, in which the subject is difference and positioned opposite each other. It shows how the school from its function as a mechanism of historical tuning of the subject and dissemination of normative parameters of society, as scientists and academics of humanity achievements, you can get to claim the difference and to defend it as a focus of building indeed, to avoid reducing it to a single universal truth, which historically have derived the greatest conflicts in society.